Pengembangan LKPD Biologi Materi Keanekaragaman Hayati Terintegrasi Higher Order Thinking Skills - Royani, Ida; Imran, Ali; Fitriani, Herdiana (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
LKPD is a teaching material product that is often used by teachers. The development of LKPD that integrates HOTS questions is needed to increase students' motivation and science process activities. This study aims to determine the validity, and feasibility of using LKPDs integrated with HOTS in class X biodiversity biology material at Al-Hamzar High School. The research method with the type of research is the development of the 4D model (Defaine the definition stage of development needs, Designe the LKPD design stage, Develop the LKPD manufacturing stage with expert validation, and Disseminate the dissemination stage through limited trials). The research instrument used hots-based LKPD and expert validation sheets.Â The results of the research on the validation results of teaching materials with a score range of 159.99 <X with a very feasible category and on the material validation sheet are valid with several revisions by three expert validators, namely teaching material validators, material validators and language validators. HOTS LKPD is used in the learning process to determine the extent to which students understand the biodiversity of living things.